2005
DOI: 10.1074/jbc.m509461200
|View full text |Cite
|
Sign up to set email alerts
|

Sources of NADPH in Yeast Vary with Carbon Source

Abstract: Production of NADPH in Saccharomyces cerevisiae cells grown on glucose has been attributed to glucose-6-phosphate dehydrogenase (Zwf1p) and a cytosolic aldehyde dehydrogenase (Ald6p) (Grabowska, D., and Chelstowska, A. (2003) J. Biol. Chem. 278, 13984 -13988). This was based on compensation by overexpression of Ald6p for phenotypes associated with ZWF1 gene disruption and on the apparent lethality resulting from co-disruption of ZWF1 and ALD6 genes. However, we have found that a zwf1⌬ald6⌬ mutant can be constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
127
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(131 citation statements)
references
References 35 publications
3
127
1
Order By: Relevance
“…Le Moan et al [55] also reported a substantial level of protein-thiol oxidation in glucose-grown yeast cells, and found that the presence of hydrogen peroxide increased the oxidation state of some of these proteins. We previously found that NADPH is required more for biosynthetic reactions than for resistance to oxidative stress in yeast cells growing on glucose [12]. With fermentative growth, macromolecular synthesis is rapid but respiratory rates are relatively slow.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Le Moan et al [55] also reported a substantial level of protein-thiol oxidation in glucose-grown yeast cells, and found that the presence of hydrogen peroxide increased the oxidation state of some of these proteins. We previously found that NADPH is required more for biosynthetic reactions than for resistance to oxidative stress in yeast cells growing on glucose [12]. With fermentative growth, macromolecular synthesis is rapid but respiratory rates are relatively slow.…”
Section: Discussionmentioning
confidence: 99%
“…In genetic studies using the yeast Saccharomyces cerevisiae [9][10][11][12], we determined that the major enzymatic sources of NADPH for antioxidant functions are two cytosolic enzymes: glucose-6-phosphate dehydrogenase (Zwf1p) which catalyzes the first step in the oxidative branch of the pentose phosphate pathway, and NADP + -specific isocitrate dehydrogenase isozyme 2 (Idp2p) which catalyzes the oxidative decarboxylation of isocitrate to form α -ketoglutarate. Others previously demonstrated that disruption of the yeast ZWF1 gene, which is constitutively expressed, produced only mild growth phenotypes including methionine auxotrophy and sensitivity to exogenous hydrogen peroxide in cells grown with glucose as the carbon source [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NADPH needed for biosynthesis is produced by the oxidative branch of the pentose phosphate pathway and by aldehyde dehydrogenase, encoded by ALD6 (Grabowska and Chelstowska, 2003;Minard and McAlister-Henn, 2005). NADPH is also required for antioxidation involving glutathione and/or thioredoxin, especially during oxidative metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to FBPase, the cytosolic enzyme malate dehydrogenase (MDH2) is subjected to rapid degradation when glucosestarved cells are replenished with fresh glucose (42,43). Mu-tagenesis studies have shown that the first 12 amino acids at the N terminus in MDH2 (⌬nMDH2) are essential for degradation.…”
mentioning
confidence: 99%